Sistem Informasi Laporan Harian Kinerja Pegawai Kontrak berbasis Web Pada Kantor Satpol PP dan WH Aceh - Alam, Arjuansyah; Imilda; Iqbal, Taufiq (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2023)
This research aims to analyze and evaluate the information system for daily reports on the performance of contract employees at the Aceh Satpol PP and WH offices. In this research, we conducted an in-depth analysis of various aspects of existing information systems, including the types of reports produced, the efficiency of using web-based systems, and the accessibility benefits provided by designing web-based applications. The results of the analysis show that the information system is capable of producing various types of reports, such as contract employee reports, daily, monthly, annual and recapitulation reports. The use of a web-based system with HTML and MySQL has proven to be efficient and effective, making it easier for employees to report their daily performance. In addition, designing web-based applications provides benefits in the form of easier accessibility for employees, allowing them to quickly and efficiently retrieve the information they need. To improve more optimal results from the implementation of this system, several suggestions have been proposed. First, the Aceh Satpol PP and WH offices are advised to immediately implement a web-based contract employee performance reporting information system to speed up and facilitate the process of inputting daily work data. Furthermore, it is recommended to back up data regularly to avoid the possibility of data loss or damage due to unexpected disruptions. Finally, you should consider using an internal server for this application to ensure that the data processing process can run without interference from unwanted external sources. By implementing these suggestions, it is hoped that the implementation of this information system can run more smoothly, efficiently and effectively, providing optimal benefits for users at the Aceh Satpol PP and WH offices.